2012
DOI: 10.1371/journal.pone.0047374
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analyses of Endometriosis-Related Polymorphisms in the Estrogen Synthesis and Metabolism-Related Genes

Abstract: Endometriosis is determined by genetic factors, and the prevalence of genetic polymorphisms varies greatly depending on the ethnic group studied. The objective of this study was to investigate the relationship between single nucleotide polymorphisms (SNPs) of 9 genes involved in estrogen biosynthesis and metabolism and the risks of endometriosis. Three hundred patients with endometriosis and 337 non-endometriotic controls were recruited. Thirty four non-synonymous SNPs, which change amino acid residues, were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
0
17
0
1
Order By: Relevance
“…CYP19A1 gene polymorphism is associated with reduced aromatase activity, which can lead to the development of endometriosis (Wang et al, 2010;Zaree et al, 2015;Hosseini et al, 2016;Abu Hashim, 2016). While previous studies have investigated the association between CYP19A1 and risk of endometriosis, the results were inconsistent (Hur et al, 2007;Vietri et al, 2009;Yang et al, 2010;Szczepańska et al, 2013;Wang et al, 2012Wang et al, , 2014. We have shown that there is a significant correlation between CYP19A1 rs2899470 and risk of endometriosis in a Chinese population.…”
Section: Discussionmentioning
confidence: 58%
“…CYP19A1 gene polymorphism is associated with reduced aromatase activity, which can lead to the development of endometriosis (Wang et al, 2010;Zaree et al, 2015;Hosseini et al, 2016;Abu Hashim, 2016). While previous studies have investigated the association between CYP19A1 and risk of endometriosis, the results were inconsistent (Hur et al, 2007;Vietri et al, 2009;Yang et al, 2010;Szczepańska et al, 2013;Wang et al, 2012Wang et al, , 2014. We have shown that there is a significant correlation between CYP19A1 rs2899470 and risk of endometriosis in a Chinese population.…”
Section: Discussionmentioning
confidence: 58%
“…Non-synonymous polymorphisms of CYP19A1 gene may modulate (CYP19A1) the risk of endometriosis in Taiwanese Chinese women (155,156). AA and CC genotypes were significantly represented in Val80 and 1558G/T polymorphisms of CYP19 in patients affected with endometriosis (157).…”
Section: Cyp19 Cytochrome P450 Family 19mentioning
confidence: 97%
“…Non-synonymous polymorphisms of the FSHR gene may modulate the hormone receptor risk of endometriosis in Taiwanese Chinese women (155,156). Both the GG (680Ser/Ser) and GA (680Ser/Asn) genotypes of FSHR were associated with a significantly lower risk of endometriosis (177).…”
Section: Fshr Follicle Stimulatingmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes belong to diverse groups, both functionally as well as spatially. However, a strong association has been detected between single nucleotide polymorphisms (SNPs) in hormone receptor and metabolism related genes and endometriosis in Taiwanese Chinese Women [ 41 ]. A study in Taiwanese women also showed that MUC17 polymorphisms are involved in endometriosis development and associated infertility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%